Chitosan treatment and storage temperature in the retardation of fruit ripening of red guava (Psidium guajava) - ENDANG ANGGARWULAN; WIDYA MUDYANTINI; ISNA JATI ASIYAH (Smujo International, 2015)
Abstract. Anggarwulan E, Mudyantini W, Asiyah IJ. 2015. Chitosan treatment and storage temperature in the retardation of fruit ripening of red guava (Psidium guajava). Nusantara Bioscience 7: 153-159. Guava (Psidium guajava L.) is a thin-skinned tropical fruit which is easy to ripe and rot. The objective of the study is to determine the effect of chitosan coating and storage temperature in restraining the ripening of guava and also to the combination of treatments which could be longest to lengthen its storage period. This study uses Completely Randomized Design, with two factors. The first factor is chitosan concentration of 0, 1, 2, and 3%, while the second factor is the storage temperature in 16°C and 28°C with three repetitions during four weeks. The quality of Psidium guajava which is observed during the storage is weight-loss, water content, fruit texture, reducing sugar content, vitamin C content, pigment rind (chlorophyll and carotenoid), respiration rate, and ethylene content. The treatment of chitosan concentration and the storage temperature of 16oC are able to maintain the fruit hardness, vitamin C content, and chlorophyll content; meanwhile, it shows a decrease in weight-loss, reducing sugar, respiration rate, and ethylene content. The combination of chitosan treatment of 3% with a temperature of 16°C is able to maintain the quality and to lengthen the storage period of Psidium guajava up to four weeks.